Invasive species in grassland habitat: an ecological threat to the greater one-horned rhino (Rhinoceros unicornis) - Lahkar, Bibhuti; Talukdar, Bibhab; Sarma, Pranjit (Pachyderm, 2011)
The successes achieved in Assam towards conservation and management of greater one-horned rhinos (Rhinoceros unicornis) are often overshadowed by a few poaching incidences. Rhino conservation efforts made by the Assam Forest Department, assisted by communities and civil society organizations, have made it possible to downgrade the status of greater one-horned rhinos from Endangered to Vulnerable on IUCN’s 2008 Red Lists of Threatened Species. One of the major threats besides poaching is the slow and steady intrusion of invasive species in grassland habitats, which directly reduces suitable flora for rhinos and other herbivores. This matter has not yet been highlighted to attract conservation intervention and support. The increasing invasion of weeds that has been observed in Nepal and India’s grassland habitats in the past decade needs scientific intervention to ensure the long-term conservation of rhino habitats. Based on available information, we portray the threats posed by invasive species towards the survival of greater one-horned rhinos in India and Nepal. Key words: greater one-horned rhino, invasive species, management, threats, grassland Les succès obtenus dans l’Assam dans la conservation et la gestion du grand rhinocéros unicorne (Rhinoceros unicornis) sont souvent obscurcis par quelques incidences de braconnage. Les efforts faits par le Département des Forêts de l’Assam pour conserver le rhinocéros, assisté par les communautés et les organizations de la société civile, ont permis de déclasser l’inscription du grand rhinocéros unicorne d’une Espèce menacée de disparition à une Espèce vulnérable sur les Listes rouges de l’UICN de 2008. L’une des principales menaces qui pèsent sur ces animaux à part le braconnage c’est l’intrusion lente et régulière des espèces envahissantes dans les habitats des herbages, ce qui réduit directement les essences adaptées aux rhinocéros et aux autres herbivores. Cette question n’a pas encore été mise en exergue pour attirer l’intervention et le soutien à la conservation. L’invasion croissante des mauvaises herbes qu’on a observée dans les habitats des herbages du Népal et en Inde au cours de la dernière décennie nécessite une intervention scientifique pour veiller à la conservation à long terme des habitats de rhinocéros. Selon les informations disponibles, nous décrivons les menaces posées par les espèces envahissantes à la survie des grands rhinocéros unicornes en Inde et au Népal.